Integrative Analysis of LGR5/6 Gene Variants, Gut Microbiota Composition and Osteoporosis Risk in Elderly Population - Di, Dong-sheng; Li, Can; Dai, Yu; Wei, Mu-hong; Wang, Shan-shan; Song, Wen-jing; Zhou, Hao-long; Cui, Yuan; Zhang, Ru-yi; Huang, Qin; Wang, Qi (Frontiers in Microbiology, 2021)
Objective: This study aimed to explore the relationships between the common variants of R-spondin/Wnt signaling genes, gut microbiota composition, and osteoporosis (OP) risk in elderly Chinese Han population. Design: Dual-energy X-ray absorptiometry was used to obtain the OP-associated measurements at multiple skeleton sites among all 1168 participants. Genotyping data was obtained by using the next-generation sequencing in the discovery stage (n = 400, 228 OP patients) and SNPscan technology in the replication stage (n = 768, 356 OP patients). Bioinformatic analysis was performed to provide more evidence for the genotype-OP associations. The 16S ribosomal RNA gene high-throughput sequencing technology was adopted to explore OP-associated gut microbiota variations. Results: The genetic variants of rs10920362 in the LGR6 gene (P-FDR = 1.19 × 10-6) and rs11178860 in the LGR5 gene (P-FDR = 1.51 × 10-4) were found to associate with OP risk significantly. Several microbial taxa were associated with the BMDs and T-scores at multiple skeleton sites. The associations between rs10920362 and BMD-associated microbiota maintained significance after adjusting confounders. The rs10920362 CT/TT genotype associated with a decreased relative abundance of Actinobacteria (β = -1.32, P < 0.001), Bifidobacteriaceae (β = -1.70, P < 0.001), and Bifidobacterium (β = -1.70, P < 0.001) compared to the CC genotype. Conclusion: Our findings suggested that the variants loci of LGR6 may be associate with OP pathogenesis via gut microbiota modifications. The relationship between host genetics and gut microbiome provides new perspectives about OP prevention and treatment.